A 'donut effect'? Assessing housing transactions during COVID-19 across the Spanish urban–rural hierarchy. Issue 1 (31st December 2023) - González-Leonardo, Miguel; Rowe, Francisco; Vegas-Sánchez, Arturo
ABSTRACT: We assess if a 'donut effect' has occurred in Spain during the COVID-19 pandemic. Our results show a synchronized 30% drop in housing purchases during the national lockdown in 2020, followed by a significant increase from 2021 across the rural-urban continuum, including core cities, suburbs, towns and rural areas, exceeding pre-pandemic levels. We thus found no evidence of a 'donut effect' in Spain.